Calculating earth dam seepage using HYDRUS software applications - Jakub Nieć; Paweł Zawadzki; Zbigniew Walczak; Marcin Spychała (Acta Scientiarum Polonorum. Formatio Circumiectus)
This paper presents simulations of water seepage within and under the embankment dam of Lake Kowalskie reservoir. The aim of the study was to compare seepage calculation results obtained using analytical and numerical methods. In April 1985, after the first filling of the reservoir to normal storage levels, water leaks was observed at the base of the escarpment, on the air side of the dam. In order to control seepage flow, drainage was performed and additional piezometers installed. To explain the causes of increased pressure in the aquifer under the dam in May 1985 a simplified calculation of filtration was performed. Now, on the basis of archived data from the Department of Hydraulic and Sanitary Engineering using 3D HYDRUS STANDARD software, the conditions of seepage under the dam have been recreated and re-calculated. Piezometric pressure was investigated in three variants of drainage, including drainage before and after modernization.